Widening global access – the need for a paradigm shift from excellence to responsibility in international higher education. (17th January 2012) - Lenger, Alexander; Schneickert, Christian; Schumacher, Florian
This paper analyses the issue of widening global access, i.e., increasing opportunities for people from the developing countries from the Global South to participate in international higher education. Following Bourdieu it is argued that there are class specific patterns to higher education hidden by the neoliberal postulate of excellence. Using Wallerstein's global system analysis a brief discussion of the global structure is presented. Thereafter, a normative framework is developed using the idea of inclusion and capabilities to legitimise Widening Global Access. Since the capabilities are reproduced unequally the need is for widening participation of students from the developing countries. Widening Global Access means that the comparison between students from the industrialised and developing countries cannot be done on an absolute level but rather a relative approach taking into account the unequal starting position must be applied.